Risk Assessment of Shallow Landslides for Infrastructure Projects: Analysis of the Case of a Landslide in the El Cabuyal Zone (2018)
In this paper an assessment of the hazard, the vulnerability and the risk associated with shallow landslides in a watershed of the Valle de Aburra is carried out. The TRIGRS model with a Monte Carlo simulation to estimate the probability of failure in the watershed using water table depth as the trigger factor is implemented, which allows the assessment of the hazard along with its annual probability of occurrence. Additionally, a quantitative model for physical vulnerability of structures which takes into account landslide intensity and resistance of exposed elements is used. The annual risk is estimated for a house of the study site as the product of the hazard and the damage costs due to the occurrence of the catastrophic event, which considers vulnerability. The methodology used focuses on the shallow landslide occurred on October 26, 2016 on a slope within the study site, which affected the house that is being analyzed.